Linking maritime security and sustainability: Naval strategy and multilateral engagements toward SDG 14 and SDG 16 - Syahnaz, Raesha; Supriyadi, Asep Adang; Yudo, Lukman (Institute for Advanced Science Social, and Sustainable Future, 2026)
Background: Indonesia’s strategic position between the Indian and Pacific Oceans, particularly at the Sunda and Lombok Straits, makes it a key actor in Indo-Pacific maritime security. Amid growing global geopolitical rivalries, this study analyzes Indonesia’s efforts to balance defense interests, strategic neutrality, and regional cooperation. This focus supports the achievement of SDG 16 and SDG 14 through transparent, collaborative, and sustainable maritime governance. Methods: A qualitative approach was employed using document analysis of Indonesia’s defense policies and regional security cooperation frameworks. Findings: Indonesia is actively modernizing its naval capabilities and enhancing maritime domain awareness. Despite challenges such as resource limitations and coordination inefficiencies, the country balances strategic neutrality with multilateral engagement. Conclusion: This study emphasizes the strategic importance of managing the Sunda and Lombok Straits to balance maritime security and environmental sustainability. Indonesia’s naval posture through capacity, neutrality, and cooperation supports sovereignty, stability, and SDG 14 and 16. The paper calls for specific policies, including regional governance mechanisms, sustainability clauses in defense cooperation, and integration of naval and conservation policies to strengthen Indonesia’s role as a sustainable and resilient global maritime fulcrum. Novelty/Originality of this article: This study offers new insights into the dynamic relationship between Indonesia’s national defense strategies and the complex geopolitical realities of the Indo-Pacific maritime region, highlighting the balance between sovereignty, neutrality, and multilateralism.